1999
DOI: 10.1088/0953-8984/11/48/319
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of Al-doped a-Si:H films

Abstract: The effect of doping on a-Si:H film optical constants was studied. Evaporated films were doped with Al for making p-type material. The optical energy gap E g decreased with increase in doping concentration. The Urbach parameter increased with doping. The refractive index decreased with increasing Al concentration showing a sharp rise in dispersion curve for p + samples. The absorption coefficient increased with doping and the absorption edge shifted to lower energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Further increase of the Al concentration resulted in a further reduction of the optical band gap to 0.6 eV, as derived from UV-Vis NIR data. This is in agreement with El-Naggar and Bakry 10 and Talukder et al, 18 who reported a continuous decrease in optical band gap upon doping aSi with Al. They attributed this decrease of the measured optical band gap to an increase in disorder of the material, owing to doping.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…Further increase of the Al concentration resulted in a further reduction of the optical band gap to 0.6 eV, as derived from UV-Vis NIR data. This is in agreement with El-Naggar and Bakry 10 and Talukder et al, 18 who reported a continuous decrease in optical band gap upon doping aSi with Al. They attributed this decrease of the measured optical band gap to an increase in disorder of the material, owing to doping.…”
supporting
confidence: 91%
“…This indicates that our aSi:H x films contain more hydrogen than those in Ref. 10. Doping aSi with Al results in a p-doped material.…”
mentioning
confidence: 57%
See 3 more Smart Citations